2019
DOI: 10.1016/j.vas.2019.100059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anti-hepatitis E virus antibodies in domestic animal from three representative provinces of Burkina Faso

Abstract: Four major genotypes of Hepatitis E virus (HEV) have been documented worldwide (1–4) with genotypes 1 and 2 found in human in Sub-Saharan Africa. Human Hepatitis cases due to HEV genotype 3 and 4 are zoonotic with various animal identified as possible reservoirs. Recently, HEV genotype 3 was found in pigs and human beings in West Africa, which may change the epidemic in human. Here, we assessed the prevalence of HEV antibodies in various domestic and wild mammalians in Burkina Faso. Random sampling was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Other studies investigating HEV in cattle have produced negative or mixed results; a study in Beijing, China identified 29.4% of cattle were seroprevalent for HEV, but no HEV RNA could be detected (Chang et al 2009). A study in Burkina Faso also found 26.4% of 72 cattle to be seroprevalent for HEV (Ouoba et al 2019). Another study in Germany testing 400 milk samples found no evidence of HEV RNA, although G4 HEV is much less commonly reported in Europe than in Asia (Baechlein and Becher 2017).…”
Section: Hev In Other Land Animals and Animal Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies investigating HEV in cattle have produced negative or mixed results; a study in Beijing, China identified 29.4% of cattle were seroprevalent for HEV, but no HEV RNA could be detected (Chang et al 2009). A study in Burkina Faso also found 26.4% of 72 cattle to be seroprevalent for HEV (Ouoba et al 2019). Another study in Germany testing 400 milk samples found no evidence of HEV RNA, although G4 HEV is much less commonly reported in Europe than in Asia (Baechlein and Becher 2017).…”
Section: Hev In Other Land Animals and Animal Productsmentioning
confidence: 99%
“…In Turkey, 18.5% of goat milk samples were reported positive for HEV RNA (Demirci et al 2019 ). Meanwhile in Burkina Faso, 28.4% of 81 goats were found to have anti-HEV antibodies (Ouoba et al 2019 ). In the USA however, Sanford et al ( 2013 ) suggested that a HEV-related agent was causing HEV in goats after discovering a seroprevalence of 16% but a lack of any HEV RNA; however, this again calls into question the accuracy of HEV ELISAs.…”
Section: Hev In Other Land Animals and Animal Productsmentioning
confidence: 99%
“…In Nigeria, cases of human HEV outbreaks have been reported [ 30 , 31 ]. Further, serological evidence of HEV is known from swine, rabbits, goats, sheep, cattle [ 32 , 34 , 35 ], and a 14.6% seroprevalence of aHEV was recently reported in layer chickens in Nigeria [ 36 ]. Only one study conducted in Ogun and Lagos Statesfound aHEV RNA in chicken feces samples.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis E is endemic in several low-income countries in Africa [ 29 ]. In Nigeria, HEV is associated with sporadic cases and outbreaks in humans [ 30 , 31 ] and serological evidence has been reported from swine, rabbits, goats, hares, sheep, cattle, and layer chickens [ 32 , 33 , 34 , 35 ]. Until recently, when aHEV seroprevalence of 14.6% was reported in commercial layer chickens in Southwestern Nigeria [ 36 ], there was no report of the detection of aHEV antibodies among the chicken population in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…• A wide spatial distribution of HEV was detected in small ruminant populations in southern Spain. multi-species ELISA has also been previously used in other ungulate species, including sheep and goats (Kukielka et al, 2015;Ouoba et al, 2019). The sensitivity and specificity of the assay have been established at 99.2%.…”
Section: Impactsmentioning
confidence: 99%